EKSISTENSI PERMAINAN TRADISIONAL PADA ERA MODERNISASI DI DESA PARENGAN KABUPATEN MOJOKERTO - Bella Aprilia (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
Traditional games are the hereditary and joyful ones. Along with time development traditional games have changed in modern era, indicated with the emergence of new technologies and modern games. Modern games have changed the patterns of people’s behavior from congregational to individualistic. Modern games are always considered as the activity to spend leisure time which is interpreted as wasting money, while traditional games are not wasting. The research aims to determine the existence of traditional games in the technological development in society and the consequences caused by modern games. The method used was descriptive qualitative explaining a phenomenon existing in society and then analyzing it using qualitative analysis. The research theory used was Heiddeger’s Existence Theory. The results of study suggest that traditional games in Parengan village still exist even though only a few games are played amid modernization. Even though there are some changes in modern games in society, it is necessary to socialize the importance of hereditary traditional games. This is because traditional games are not lost or lost due to the incoming western culture.